Comment on "Propionaldehyde infrared cross–sections and band strengths" by B. Köroğlu et al. [1]. (August 2016) - Richter, Wagner Eduardo; Bruns, Roy Edward
Abstract: The propionaldehyde infrared regional integrated area reported by Köroğlu et al. were re-examined. Even though the spectrum seems to be recorded correctly, the comparison between their values with the data obtained by the integration of the propionaldehyde spectrum available in the PNNL database suggests that a scaling factor of 2.3025 (the ratio between ln and log bases) is the reason for their results being lower than those expected based on other literature values and quantum chemical estimates. Revised values were then reported for the four spectral regions evaluated by these authors, resulting in a much better agreement between both theoretical and experimental results for not only for this molecule but also for others like acetone and acetaldehyde. Highlights: An inconsistency for propionaldehyde band strengths is clarified. Revised values are reported for the four spectral regions originally examined. Good agreement with related molecules and ab initio results is now achieved.